1990
DOI: 10.1007/bf03259203
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Randomised Study of Metronidazole (Flagyl®) 1% Cream in the Treatment of Acne Rosacea

Abstract: A double-blind. placebo-controlled study was conducted with 100 adult patients presenting with acne rosacea. 50 patients were randomly assigned to treatment with metronidazole I % cream, while the other 50 patients received placebo cream. The cream was applied morning and evening in a dose of 0.25 cm 2 per application. Clinical assessments were performed prior to drug administration and after I and 2 months of treatment.The number and severity of rosacea lesions (papules and pustules) were significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…8,10 The reduction in erythema score of 41% from baseline in the present study is also within the range observed in previous investigations: 35% 6 -90%. 10 While the 12-week duration of the current study is longer than that of previous studies, significant improvement in inflammatory lesion count and erythema was first noted at week 4 (first observation visit) and week 8 for these parameters, respectively.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…8,10 The reduction in erythema score of 41% from baseline in the present study is also within the range observed in previous investigations: 35% 6 -90%. 10 While the 12-week duration of the current study is longer than that of previous studies, significant improvement in inflammatory lesion count and erythema was first noted at week 4 (first observation visit) and week 8 for these parameters, respectively.…”
supporting
confidence: 89%
“…[6][7][8][9][10] The 65% reduction in total inflammatory lesions (papules and pustules) from baseline counts observed in the present study …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many double-blind, placebo-controlled trials of topical metronidazole have demonstrated beneficial effects in the treatment of rosacea. [10][11][12][14][15][16][17][18][19][20] Breneman et al compared the efficacy of once-daily metronidazole 1% cream with that of the vehicle alone in 139 patients. Significant reductions in inflammatory lesions were reached at 4 weeks.…”
Section: Metronidazolementioning
confidence: 99%
“…4,5 Color scales were used to assess the degree of erythema by several authors. [6][7][8] Several authors used specialized equipment to assess skin changes, especially in regard to the degree of erythema and color change in rosacea, [9][10][11] and one author examined histologic changes in affected skin. 12 While some of these methods may have improved the internal validity of the observations made in these studies, none of these techniques were described or validated well enough to promote their general use in other studies.…”
mentioning
confidence: 99%